(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
Many Village-Owned Enterprises (BUMDes) had their operational activities halted due to weak consumer purchase decisions. The factors influencing the level of purchase decisions are the marketing mix and service quality. This study aims to determine the impact of the marketing mix and service quality on retail purchase decisions at BUMDes Wijaya Kusuma in Tabanan. The population for this study consist of all consumers who have shopped at BUMDes Wijaya Kusuma. The sample size for this study is 100 respondents, using accidental sampling method. The study is analyzed using multiple linear regression techniques. The result show that, partially, the marketing mix has a positive and significant effect on purchase decisions; service quality has a positive and significant effect on purchase decisions; and simultaneously, both the marketing mix and service quality have a positive and significant effect on purchase decisions. The researcher’s recommendation is for BUMDes Wijaya Kusuma to evaluate its pricing to develop competitive pricing policies and to hire more staff to respond quickly, attentively, and effiently to consumer demands or needs. Another suggestion is for BUMDes Wijaya Kusuma to add a variety of product to ensure that they always have the products needed by consumers.